PENGARUH KUALITAS LAYANAN-E, KEPUASAN-E, DAN KEPERCAYAAN-E TERHADAP KESETIAAN-E PADA GOJEK - Margaretha Pink Berlianto (Universitas Bunda Mulia, 2017)
Daring service provider business is growing rapidly at this time, followed by fierce competition between daring service providers. It is very important for them to survive and win in this business competition. For that, they need to identify their service quality from their site based on customers’ perception, knowing the satisfaction of their customers, how deep the trust of their customers and how extent of their customer loyalty toward the daring service providers. The purpose of this study is to analyze e-service quality, e-satisfaction, e-trust and e-customer loyalty of Gojek. The research was conducted on service users Gojek (Go-ride) by distributing 400 questionnaires in Jakarta and Tangerang area and there were 121 questionnaires that can be used. Each variables was measured with 5 Likert scale. In this study, the validity test was using factor loading value of ≥ 0.6 and the reliability test was using the composite reliability ≥ 0.7 and variance extracted ≥ 0.50. There were fourteen hypotheses was tested in this study. The model fit and hypothesis testing was done by using SEM. The results of this study are Ease of use, E-scape, Responsiveness, Customization and Assurance which are five dimension of e-service quality that used in this study had no positive effect on e-satisfaction, e-satisfaction had an effect on e-trust, e-trust had no effect on behavioral loyalty, affective loyalty, loyalty cognitive and conative loyalty and e-satisfaction had effect on behavioral loyalty, affective loyalty, loyalty cognitive and conative loyalty.Keywords: e-service quality, e-satisfaction, e-trust, e-loyalty, e-commerce.